2008
DOI: 10.1177/030802260807100307
|View full text |Cite
|
Sign up to set email alerts
|

Practice Development: Bridging the Research-Practice Divide through the Appointment of a Research Lead

Abstract: Research suggests that while most clinicians endorse the importance of evidence-based practice, without the right culture of support and encouragement it can be difficult to achieve such practice. This paper presents an outline of one method to enhance evidence-based practice. It reports on the evaluation of a new type of occupational therapy post, a research lead based in clinical practice, and suggests that the post has the potential to bridge the research-practice divide. Based on feedback from clinicians, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Studies examining the effects of specific KT interventions have indicated that both single-and multicomponent KT interventions led to improvements in knowledge about obesity and the potential role of occupational therapists (Forhan & Law, 2009), about available outcome measures (Cook, McCluskey, & Bowman, 2007), and about EBP concepts such as posing a clinical question and appraising scientific articles (McCluskey & Lovarini, 2005). Other practice changes included increased use of outcome measures (Cook et al, 2007;McQueen, 2008), improvements in self-efficacy in using research in practice (Crist, 2010;Petzold et al, 2012), a more client-centered approach to practice (Finlayson et al, 2005;Rappolt et al, 2005), and more favorable attitudes toward EBP (Lysack, Lichtenberg, & Schneider, 2011;Petzold et al, 2012). The use of a research lead or research resource person in clinical practice settings resulted in increased confidence and focus in practitioners, helped overcome barriers to EBP, and increased research outputs (McQueen, 2008).…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining the effects of specific KT interventions have indicated that both single-and multicomponent KT interventions led to improvements in knowledge about obesity and the potential role of occupational therapists (Forhan & Law, 2009), about available outcome measures (Cook, McCluskey, & Bowman, 2007), and about EBP concepts such as posing a clinical question and appraising scientific articles (McCluskey & Lovarini, 2005). Other practice changes included increased use of outcome measures (Cook et al, 2007;McQueen, 2008), improvements in self-efficacy in using research in practice (Crist, 2010;Petzold et al, 2012), a more client-centered approach to practice (Finlayson et al, 2005;Rappolt et al, 2005), and more favorable attitudes toward EBP (Lysack, Lichtenberg, & Schneider, 2011;Petzold et al, 2012). The use of a research lead or research resource person in clinical practice settings resulted in increased confidence and focus in practitioners, helped overcome barriers to EBP, and increased research outputs (McQueen, 2008).…”
Section: Thematic Analysismentioning
confidence: 99%
“…Other practice changes included increased use of outcome measures (Cook et al, 2007;McQueen, 2008), improvements in self-efficacy in using research in practice (Crist, 2010;Petzold et al, 2012), a more client-centered approach to practice (Finlayson et al, 2005;Rappolt et al, 2005), and more favorable attitudes toward EBP (Lysack, Lichtenberg, & Schneider, 2011;Petzold et al, 2012). The use of a research lead or research resource person in clinical practice settings resulted in increased confidence and focus in practitioners, helped overcome barriers to EBP, and increased research outputs (McQueen, 2008).…”
Section: Thematic Analysismentioning
confidence: 99%
“…In occupational therapy, researchers have examined the use of clinician-scientists, evidence-based practice teams and managers to facilitate the transfer of research evidence into practice (Caldwell, Whitehead, Fleming & Moes, 2008;McCluskey & Cusick, 2002;McQueen, 2008) but no published studies exist which examine the use of CPGs more specifically. However, there are promising results in related rehabilitation fields such as physical therapy.…”
Section: Effectiveness Of Cpgsmentioning
confidence: 99%
“…Evidence-based occupational therapists use research evidence in combination with clinical knowledge and reasoning to make decisions about interventions that are effective for specific clients (Law & Baum, 1998). To date, research on evidence-based occupational therapy practice has focused on (a) the attitudes and perceptions about evidence-based practice (EBP) as well as confidence in one’s ability to use evidence in practice (Bennett et al, 2003; Cameron et al, 2005; Davis, Zayat, Urton, Belgum, & Hill, 2008), (b) the gaps between actual practice and EBP (Chard, 2006; Lyons, Casey, Brown, Tseng, & McDonald, 2010; Menon, Korner-Bitensky, & Straus, 2010), and (c) the design, implementation, and evaluation of knowledge translation (KT) strategies aimed at promoting the integration of scientific evidence in practice (Hammond & Klompenhouwer, 2005; McCluskey & Lovarini, 2005; McQueen, 2008). Despite the growing status of EBP, there is compelling evidence that available research findings are not integrated routinely in occupational therapy practice (Cameron et al, 2005; Korner-Bitensky et al, 2006; Salls, Dolhi, Silverman, & Hansen, 2009).…”
mentioning
confidence: 99%